Pengaruh Model Pembelajaran Inkuiri Terbimbing Terhadap Kemampuan Literasi Sains Siswa di SMP Negeri 35 Palembang - Yuni Erdani; Lukman Hakim; Linda Lia (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2020)
This study aimed to determine the effect of guided inquiry learning models toward of the seventh-grade students' scientific literacy on energy material. The research methodwas quasi-experimental study with Nonequivalent Control Group design. For data analyze, the test results were performed using the hypothesis testing (Independent sample t-test). The results of this study in the DI (Direct Instruction) learning in the control class were 60,20 in the pretest scores and 72,20 in the posttest scores.Meanwhile, the guided inquiry learning in the experimental class, the mean of pretest scores was 66,93 and the mean of posttest scores was 83,00. Hypotheses testing the ability of scientific literacy found sig-tailed value of 0.00, because the value of sig <0.05, It meant that H0was rejected and H1 was accepted. Based on the data, it could be concluded that the guided inquiry learning model had significant difference on the literacy ability of the seventh grade students on energy material.